Analisis Penggunaan Media Sosial Terhadap Kualitas Tidur Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Islam - Fathin Nur Muhammad; Firman Hidayatullah; Muhammad Saddam Al Andalusi; Wahyu Hidayat (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
This study aims to analyze the relationship between the use of social media and sleep quality in FEBI students. This study uses an analytical observational research design with a cross sectional approach. Data was collected using a questionnaire consisting of information about social media usage and sleep quality. The results showed that there was a weak correlation between social media use and sleep quality (ρ=0.004, R=0.506). This shows that excessive use of social media can interfere with the quality of students' sleep